Scientific Evaluation of Safety and Efficacy of Panchagavya Formulation: A Scoping Review - Mohanan, Deepu; Rammanohar, P; Pillai, Zeena S (International Journal of Innovative Research and Scientific Studies, 2025)
Within the realm of Ayurveda, the ancient Indian medicinal system, the Panchagavya formulation has been utilized to address various human ailments. The Panchagavya blend, derived from five key bovine products (cow milk, curd, ghee, urine, and dung), has been proposed as an alternative, preventive, and healing method for both poultry and human health. Immunostimulant, antioxidant, hepatoprotective, anti-stress, anti-epileptic activities, nootropic effects, anxiety, and mental retardation are the well-investigated areas of interest. According to Ayurveda practitioners, the Panchagavya formulation has therapeutic potential in a wide range of health conditions including leukoderma, alopecia, colds, rheumatoid arthritis, allergies, cough, leucorrhoea, flu, dietary and gastrointestinal disorders, aging-related issues, renal disorders, wound healing, heart disease, skin infections, tuberculosis, chickenpox, worm infestations, hepatitis, leprosy, and various bacterial and viral infections. Enhanced body immunity is attributed to the presence of minerals, hormones, and acids such as citric, carbolic, and succinic, as well as salts like manganese, sulfur, phosphate, chloride, and sodium, along with vitamins A, B, C, D, and E. Individual components like cow's milk, curd, ghee, dung, and urine possess notable therapeutic properties within the Indian traditional medicine system; their combination likely yields synergistic pharmacological effects, as reported in recent Indian literature. Cow ghee possesses anti-cancer, anti-inflammatory, and wound healing effects. Cow milk exhibits anticancer and antihypertensive properties, while cow dung demonstrates antimicrobial and antioxidant capabilities. Curd and yogurt exhibit antihypertensive and immunomodulatory characteristics. The notable features of cow urine include its antioxidant, antibacterial, anticancer, anti-hypertensive, and wound healing effects. Nevertheless, there aren't sufficient scientific studies to support Ayurveda's medicinal claims for the Panchagavya formulation. This review delves into the available literature elucidating the diverse treatment benefits of the Panchagavya formulation in addressing various human disorders and diseases claimed by Ayurveda. The review also discusses the potential, drawbacks, current level of social acceptance, and uncritical evaluation of the Panchagavya formulation.